Retrospective Review of Adrenalectomy in a Tertiary Center in Nepal - Dhital, Pawan; Rai, Bipendra DK; Pradhan, Manish; Poudyal, Sujeet; Chapagain, Suman; Chalise, Pawan R; Luitel, Bhoj R; Sharma, Uttam K; Gyawali, Prem R (Journal of Institute of Medicine Nepal, 2019)
Introduction: Adrenal gland surgery is a challenging art as it encompasses diverse physiological derangements which are even life-threatening. Also, it remains a medical finesse to rightly identify the correct patient who will benefit from surgery which include strong biochemical and radiological resource. Soundly performed surgery will lead to oncologic and homeostatic correction leading to near normal course. Methods: This is a retrospective analysis of adrenalectomy cohort over three years in a tertiary center in Nepal identifying diagnosis, preoperative management and postoperative course. The objective of this study is to review the presentation, histopathology and clinical outcomes of patients operated for adrenal mass in our center. Results: There were 42 surgeries performed via open approach. The number of adenoma, phaeochromocytoma, carcinoma and non-functioning tumor were 13, 16, 12 and one respectively. In most of the hypertensive patients, control was achieved with minimal drug and recurrences were observed in 25% of carcinoma in postoperative follow up. Conclusion: A large proportion of operative adrenal mass are observed clinically in our setup. The surgical outcome is satisfactory but judicious perioperative management is essential.